Role of Local/Community Radio on Rural Development - Timalsina, Mahanand; Pradhan, Prajwal Man (Nepalese Journal of Development and Rural Studies, 2019)
This paper renders role of local/community radio on rural development in general and rural community development process in particular. By applying library based research method, necessary informations are generated through literature review. This paper highliths that community radio has brought positive impacts particularly in  seven thematic areas (i.e. suitability, agricultural transformation, promoting participatory democracy, voice of voiceless, information/ discussion forum on local issues, empowering unprivileged rural people and contribution on good governance). Thus, better to offer radio programs by the local level authorities in such thematic areas for strengthning rural development process in general and rural community development process in particular.